Sterile pyogranulomatous nodular panniculitis in a cat - case report - A. Silvio Neto; D.D. Moreira; J.V.G. Oliveira; B.B. Santos; J.C.A. Machado; M.L.P. Maia; D.S.B. Yamamoto (Arquivo Brasileiro de Medicina Veterinária e Zootecnia)
ABSTRACT Sterile nodular pyogranulomatous panniculitis is an inflammatory disease of variable extent and severity, considered uncommon in dogs and rare in felines. The aim of this study was to report the case of a feline with sterile nodular pyogranulomatous panniculitis responsive to pharmacological treatment. A male, mixed breed cat, weighing 4 kg, aged one year, was treated with a history of a single, ulcerated, erythematous, slightly irregular and firm nodule. Complete blood count, biochemical tests, cytology of the nodule, culture, radiography and histopathology were requested. The definitive diagnosis was obtained through histopathological examination and the established treatment, with prednisolone at a dose of 1 mg/kg, BID, for the first ten days, subsequently reduced to SID for another 10 days, associated with dipyrone 1 drop/kg, BID, for 5 days, was sufficient for the remission of the lesion. It is concluded that Sterile nodular pyogranulomatous panniculitis is a rare disease in felines, but important considering the wide diversity of differential diagnoses, and that in the case of a single nodular presentation, clinical treatment was sufficient for complete remission, and histopathology was the determining exam for diagnostic confirmation.